Mätosäkerhet och processvariation avseende kiseldioxidhalt vid kulsintring : En fallstudie vid LKAB, Kiruna - Burlin Andersson, Oscar (2013)
Today there is a strong competition within the iron ore market. In order to be a great competitive on the market LKAB considers that one of their best competitive advantages is customer satisfaction. Through continuous improvement in product quality control and statistical process control can LKAB further improve their processes and ensure that the objectives that are obtained in resource efficiency, energy efficiency and reducing impact on the environment and climate will maintain. It should lead to a maintained and improved customer satisfaction. This study is initiated by LKAB in order to obtain more knowledge of the measurement error and product variation in the Pelletizing plant 2 in Kiruna so that the process control can be improved. By studying four sampling points in Pelletizing plant 2 has the measurement error of sub-sampling, sample preparation and analysis for each of the sampling points sought to be established. That has been successful in most cases. Furthermore, with the knowledge of measurement error, the product variation of the process has been determined. Finally, the aim was to suggest possibilities for a general model for the adjustment of the statistical control limits, in an earlier step in the process, if their where changes in the customer requirements. The measurement error has been calculated by collection of primary data from experiments conducted and secondary data from the daily production and earlier experiments conducted at LKAB. In the cases where the measurement error could not be calculated has a bias, differences between different measurement methods, been calculated. The calculations of the measurement error have also been able to detect what have the greatest impact on the measurement error. In order to create an impression if the LKAB tolerance limits and control limits, that are used today, are reasonable relative to the current process variation a capability study and analyzes between the LKAB control limits and possible statistical control limits where conducted. The ...